2003
DOI: 10.1046/j.1469-0691.2003.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

A European survey of diagnostic methods and testing protocols for Clostridium difficile

Abstract: The results of this study suggest marked discrepancies between laboratories and also between countries regarding the criteria by which C. difficile is investigated for, and the methods and the strategies that are used for the diagnosis of C. difficile. These discrepancies could be explained by the lack of clear guidelines for C. difficile diagnosis in each country, and by the importance that physicians attach to C. difficile. Precise guidelines for C. difficile diagnosis would be the first step to make possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
62
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 36 publications
5
62
0
Order By: Relevance
“…This study showed major discrepancies between laboratories and between countries (Barbut et al, 2003).…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…This study showed major discrepancies between laboratories and between countries (Barbut et al, 2003).…”
Section: Introductionmentioning
confidence: 66%
“…Mostly C. difficile toxin EIAs are used for the diagnosis of CDAD (Barbut et al, 2003). Stool culture is used in 20 % (Great Britain) to 100 % (Denmark) of laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…The recent European survey of diagnostic methods and testing protocols by Barbut et al (2003) clearly shows the wide variations of protocols observed among laboratories from different countries. Although most countries, except Denmark, routinely perform toxin detection on stools, the figure is quite different for culture: more than 90 % of the laboratories in Denmark and Belgium perform it but only 28 % in Spain and 20 % in the UK.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the recommendations issued in the USA and UK limit the diagnosis to a single toxindetection test on faecal specimens by cultured cells or IA, although in several other European countries both culture and toxin detection are recommended for an optimal diagnosis (Berrington et al, 2004;Bartlett, 2002;Brazier, 1998;Delmée, 2001). A recent survey has clearly shown the large variations in the methods used when comparing laboratories from different European countries (Barbut et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Toxin enzyme immunoassays are more rapid and easier to perform but are suboptimal if used as stand-alone assays due to the low sensitivity compared to CCNA or toxigenic C. difficile culture (3,7,10). Today, many laboratories rely on C. difficile toxin A/B testing alone despite the limits of this approach and have abandoned bacterial culture (2,3). Detection of the C. difficile-specific enzyme glutamate dehydrogenase antigen (GDH) may in part replace culture techniques and therefore be an alternative to culture (9,10,12,13).…”
mentioning
confidence: 99%